Prototype design of rainwater harvesting and solar irrigation system for small - scale farm - Saiful Iskandar, Khalit; Eeyad Arief, Asri; Ahmad Zaidi, Hampden (Penerbit Universiti Sultan Zainal Abidin, 2020)
The current irrigation system at Taman Tanaman Dapur that used by the Faculty of Bioresources and Food Industry (FBIM) is operated manually, and the water source is directly from Syarikat Air Terengganu (SATU). The cost incurred to maintain the current system is expensive therefore, the UniSZA fund for maintenance purpose. By observing these factors, there is an opportunity to improve the irrigation system by utilising the available natural resources in the form of sun and rain, respectively, as a source of energy and water. Thus, the objectives of this project are to design and validate the prototype of rainwater harvesting and solar irrigation system for small scale farm use. By utilising the prototype, it is possible to take advantage of the available natural resources resulting in a technological advancement that optimises the energy usage producing a cost-effective, efficient irrigation system. The prototype design was carried out using a two-dimensional computer-aided design software, AutoCAD. Furthermore, the prototype development was carried out and validated with several readily-available types of equipment in the laboratory as well as equipment that could be obtained by local farmers or individuals. As a result, after going through phases of prototype creations, from the proof of concept, through mock-up testing, and pre-production, it has been well-function as designated. The value of Gross Irrigation Requirement (GIR) for this study was 308.22 mm/month while the minimum requirement of power production from the solar panel output was 0.552 kWh. More improvement can be made for further development of the prototype by integrating with other technologies such as attach it with moisture sensor and timer for the optimum condition.